Nsp16 shields SARS–CoV‐2 from efficient MDA5 sensing and IFIT1‐mediated restriction. (26th October 2022) - Russ, Alina; Wittmann, Sabine; Tsukamoto, Yuta; Herrmann, Alexandra; Deutschmann, Janina; Lagisquet, Justine; Ensser, Armin; Kato, Hiroki; Gramberg, Thomas
Abstract: Methylation of the mRNA 5′ cap by cellular methyltransferases enables efficient translation and avoids recognition by innate immune factors. Coronaviruses encode viral 2′‐O‐methyltransferases to shield their RNA from host factors. Here, we generate recombinant SARS–CoV‐2 harboring a catalytically inactive 2′‐O‐methyltransferase Nsp16, Nsp16mut, and analyze viral replication in human lung epithelial cells. Although replication is only slightly attenuated, we find SARS–CoV‐2 Nsp16mut to be highly immunogenic, resulting in a strongly enhanced release of type I interferon upon infection. The elevated immunogenicity of Nsp16mut is absent in cells lacking the RNA sensor MDA5. In addition, we report that Nsp16mut is highly sensitive to type I IFN treatment and demonstrate that this strong antiviral effect of type I IFN is mediated by the restriction factor IFIT1. Together, we describe a dual role for the 2′‐O‐methyltransferase Nsp16 during SARS–CoV‐2 replication in avoiding efficient recognition by MDA5 and in shielding its RNA from interferon‐induced antiviral responses, thereby identifying Nsp16 as a promising target for generating attenuated and highly immunogenic SARS–CoV‐2 strains and as a potential candidate for therapeutic intervention. Synopsis: Replication of SARS–CoV‐2 harboring inactive Nsp16 is attenuated and very sensitive to type I IFN treatment. Nsp16 counteracts intrinsic restriction and sensing mechanisms, rendering Nsp16‐deficient viruses good candidates for live‐attenuated vaccine development. SARS–CoV‐2 Nsp16mut shows attenuated replication. SARS–CoV‐2 Nsp16mut replication is highly IFN sensitive. Nsp16 protects SARS–CoV‐2 from IFIT1 restriction. Nsp16 shields SARS–CoV‐2 from MDA5 sensing. Abstract : Replication of SARS‐CoV‐2 harboring inactive Nsp16 is attenuated and very sensitive to type I IFN treatment. Nsp16 counteracts intrinsic restriction and sensing mechanisms, rendering Nsp16‐deficient viruses good candidates for live attenuated vaccine development.